Model simulations of resource use scenarios for Europe - Kurt Kratena; Mark Sommer (WWWforEurope, 2014)
This paper describes the introduction of biophysical constraints into a disaggregated dynamic New Keynesian (DYNK) model using the example of different resource use scenarios for Europe, derived from global UNEP scenarios. The DYNK model covers 59 industries and five income groups of households and has similar features to a DSGE model (e.g. QUEST). The model solution converges towards a long-run full employment equilibrium, but exhibits short-run institutional rigidities (imperfect credit and capital markets, wage bargaining). The DYNK model links physical energy and material flow data to production and consumption activities. Different sources of technical change are modelled at the disaggregate level: TFP, factor-bias and material efficiency in production and energy efficiency in private consumption. These components of technical change drive - together with relative prices - economic growth and resource use and therefore decoupling. A scenario of modest resource use reduction (per capita) is implemented by shifting the bias of technological change from labour/capital saving to energy/resource saving. As one example for a scenario of radical reduction of resource use per capita, the radical reduction of energy demand and GHG emissions is analysed. The results show the various interlinkages between different categories of material flows, which lead to co-benefits of policies. Further policy options are discussed (re-use and recycling of material in key industries, structural change in agriculture) and shall be analysed in a follow-up of this paper.
Keywords: Q32; Q55; C54; 330; Decoupling of resource use; technological and structural change; policy simulation